2011
DOI: 10.17221/90/2009-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of squared timber and log products in the Hyrcanian Forests of Iran

Abstract: ABSTRACT:The forests located in the northern areas of Iran are known as Hyrcanian Forests and are distributed across three provinces, namely Gilan, Maznadarn and Golestan. These provinces are situated in the north of Iran near the Caspian Sea. Timber products in the said forests during the last two decades were markedly different so that the total timber harvested in the first decade was 1.6 million m 3 on average, however, in the second decade it nearly amounted to 1 million m 3 . Two major timber products of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In this study, the values of the saturation constant and maximum utilization rate for the Stover-Kincannon model were in the low scope of results in the other research (Table 3). Similar observations were reported by Hosseiny and Borghei [25] for synthetic wastewater. Increasing the concentrations of 4-NP and 4-t-OP when the influent COD was equal to 500 mg/L, decreased the values of U max and K B .…”
Section: First-order Kinetic Modelsupporting
confidence: 91%
“…In this study, the values of the saturation constant and maximum utilization rate for the Stover-Kincannon model were in the low scope of results in the other research (Table 3). Similar observations were reported by Hosseiny and Borghei [25] for synthetic wastewater. Increasing the concentrations of 4-NP and 4-t-OP when the influent COD was equal to 500 mg/L, decreased the values of U max and K B .…”
Section: First-order Kinetic Modelsupporting
confidence: 91%
“…Hyrcanian forests of Iran, just like other forests, have been logged under different silvicultural operations such as shelterwood and selection methods [23,27] that created different gap sizes within these forests. These forestlands are located in the northern part of Iran, also known as the Caspian forests and belong to the end of the third geological era [5]. So far, few studies have been conducted regarding the effect of gap size in hyrcanian beech forests, especially, its effects on soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…A forest station or biotope is a welldefined geographical area characterised by its relief, rock (or parental material elements), soil type, and climatic conditions. These factors all establish and determine the productivity of stands [22][23][24], as well as the forest growth globally [25,26]. Furthermore, studies have shown that precipitation and temperature are other major factors that influence forest growth [27,28].…”
Section: Methodsmentioning
confidence: 99%